Strategic management in education for quality output (2009)
This paper discussed the role of strategic management in promoting quality educational output, by looking at strategic management in education, style of management and the components of managements as tools for effective strategic management of educational resources and outlined the educational process/ transformation and output. It opined that if the strategic management in education were to be profitable it must employ the management components defined as : forecasting, planning, budgeting, organising, implementing, monitoring and evaluation, feedback and revision for improvement(FPBOIMEFR). Further, it highlighted the constituents of the things for quality output strategic management as the following resources: students (the basic input), human resources (capital)- workers of all category in the industry, fund management, equipment including communications equipment, learning materials, infrastructure and other facilities and time management and even classroom management. It concluded that strategic management in the education brings about effectiveness and efficiency, culminating in quality educational output. It was recommended that since everyone in the industry was a manager to some degree there should be specialty specific management training.